2021
DOI: 10.1002/cjce.24294
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and numerical modal analysis of wall tubes in the coal‐fired boiler or radiant syngas cooler

Abstract: The slag deposited on the wall tubes in the coal-fired boiler or radiant syngas cooler (RSC) of the entrained flow gasifier could reduce the heat transfer efficiency and degrade the tubes by corrosion. During the operation of the boiler or RSC, the rapping-off-ash method is an effective method to remove slag deposits, especially in a high-pressure environment. The operating parameters of the rapping-off-ash method are related to the modal parameters of wall tubes, including the natural frequency, damping ratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Modal analysis of the mechanical system can obtain its inherent frequency and modal vibration pattern, and then avoid resonance of the mechanical structure [12], this section uses ABAQUS to perform modal analysis of the designed fixture, and the material parameters of each component are shown in Table 6. The positive tetrahedral structure C3D10 is selected to perform uniform meshing of the model, and Figure 19 shows the model after meshing.…”
Section: Modal Analysismentioning
confidence: 99%
“…Modal analysis of the mechanical system can obtain its inherent frequency and modal vibration pattern, and then avoid resonance of the mechanical structure [12], this section uses ABAQUS to perform modal analysis of the designed fixture, and the material parameters of each component are shown in Table 6. The positive tetrahedral structure C3D10 is selected to perform uniform meshing of the model, and Figure 19 shows the model after meshing.…”
Section: Modal Analysismentioning
confidence: 99%
“…The IRA method was applied to investigate the vibration modal of water wall‐tubes by our team. [ 9 ] Modal parameters (the natural frequency, damping ratio, and mode shapes) of wall tubes composed of three tubes and fins were studied through the modal tests and numerical simulation based on the finite element method. The numerical result was similar to the experiment within 10% bias, which indicated that the numerical method was a reliable method to study the modal characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, based on the preliminary work, [ 9 ] IRA was further developed using a real RSC as the object. Model establishment was conducted based on the finite element software ABAQUS, [ 28 ] and the natural vibration characteristics were revealed by modal analysis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation